THE POTENTIAL OF FOREST HONEY (Apis spp) FROM TIMOR ISLAND AS ANTIBACTERIAL AGAINST PATHOGENIC BACTERIA IN FISH CULTURE - yuliana Salosso (Indonesian Aquaculture Journal, 2019)
This study aims to know the potential of forest honey Apis spp. from Timor Island as antibacterial on pathogenic bacteria Aeromonas hydropilla and Vibrio alginolyticus in cultured fish, through testing of active compound, total glucose, pH and water content of the honey, that play the role in antibacterial mechanisms in honey. Chemical content of the honey was examined for alkaloid using Culvenor-Fiztgerald method, saponin with foam test, terpenoid and steroid with Lieberman-Burchard method, tannin with addition of FeCl3, and flavanoid addition of HCl and Mg powder. Total glucose was measured using spectrophotometer, water content with gravimetry, and pH with pH-meter. The antibacterial activity  test of the honey was done using disc method without dilution. Results showed that all forest honey from Timor Island contained alkaloid, saponin, steroid and terpenoid, except that Kefa honey did not hold steroid and terpenoid. Water content of the honey ranged from 15.70% to 26.65%, total glucose of 71.16% to 80.58%, and pH of 3.84 to 4.06. The forest honey had also antibacterial activity against A. hydropilla and V. alginoliticus with different inhibition zone.